Erratum: Lupeol, a dietary triterpene, enhances wound healing in streptozotocin-induced hyperglycemic rats with modulatory effects on inflammation, oxidative Stress, and angiogenesis (Oxidative Medicine and Cellular Longevity (2019) 2019 (3182627) DOI: 10.1155/2019/3182627) - Beserra, Fernando Pereira [UNESP]; Vieira, Ana Júlia [UNESP]; Gushiken, Lucas Fernando Sérgio [UNESP]; De Souza, Eduardo Oliveira [UNESP]; Hussni, Maria Fernanda [UNESP]; Hussni, Carlos Alberto [UNESP]; Takahira, Regina Kiomi [UNESP]; Nóbrega, Rafael Henrique [UNESP]; Martinez, Emanuel Ricardo Monteiro [UNESP]; Jackson, Christopher John; De Azevedo Maia, Gabriela Lemos; Rozza, Ariane Leite [UNESP]; et al. (Hindawi, 2020)
In the article titled Lupeol, a Dietary Triterpene, Enhances Wound Healing in Streptozotocin-Induced Hyperglycemic Rats with Modulatory Effects on Inflammation, Oxidative Stress, and Angiogenesis [1], Dr. Regina Kiomi Takahira was missing from the authors' list. Dr. Takahira conducted biochemical assays such as AST, ALT, ?-GT, alkaline phosphatase, creatinine, and urea, as well as the interpretation and visualization of all these data. The corrected authors' list is shown above.